Implementation of SIAPIK-Based Sustainable Accounting Digitalization to Support MSME Business Upgrading - Indriani, Jennisa Dwina; Yahaya, Rusliza Binti; Ahmad, Noor Lela Binti (Multidisciplinary Journal of Education , Economic and Culture, 2026)
This study aims to analyze the implementation of SIAPIK-based digital accounting in supporting business upgrading among MSMEs in Bukittinggi. Adopting a qualitative approach with a case study design, this research seeks to provide an in-depth understanding of the digitalization process. The informants comprised 15 MSME practitioners selected via purposive sampling, meeting the criteria of being registered entities, possessing a Taxpayer Identification Number (NPWP), and having been in operation for over two years. Data were gathered through semi-structured interviews, participatory observation, and documentation, then analyzed using the Miles and Huberman interactive model. The findings reveal four primary themes: SIAPIK as an instrument for business regularity, digitalization as a strategic driver for business upgrading, challenges in digital literacy and technological adaptation, and digital accounting as a foundation for business sustainability. The utilization of SIAPIK assists MSMEs in enhancing financial administrative order, operational efficiency, and strategic decision-making, while also facilitating access to financing and business legality.